RFID transponder integration in metal surgical instruments produced by additive manufacturing. (December 2014) - Paz, J. F. I.; Wilbig, J.; Aumund-Kopp, C.; Petzoldt, F.
Abstract : Radio frequency identification (RFID) applications are becoming more and more important in logistics, especially for the purpose of tracking and managing items. Real time tracking of medical instruments during a surgical operation belongs to the state-of-the-art applications of this technology. The metallic environment in the operating room represents a big challenge, hampering the readability of the RFID tag. Currently, transponders are joined to metal instruments by bonding or clamping them inside a polymer shell, containing as little metal as possible. Assembling the tags is a time consuming process, which changes the usual shape of the instrument. It also represents a point of failure because of the possibility of losing the tag during the instrument's life cycle. Selective laser melting (SLM) offers a way to integrate the entire RFID tag in a metallic instrument while keeping the original shape. Instrument manufacturing by SLM allows small wall thicknesses and a reduced temperature impact on the RFID tag during the building process. The production of trial components from IN718 nickel alloy is reported.